SECURITY AND PRIVACY IN THE INTERNET OF THINGS - Rameem Zahra, Syed; Ahsan Chishti, Mohammad (BOCA RATON : CHAPMAN & HALL CRC, 2020)
This book provides a comprehensive study of the security and privacy research advancements in Internet of Things (IoT). The book lays the context for discussion by introducing the vulnerable intrinsic features of IoT. By providing a comprehensive discussion of the vulnerable features, the book highlights the problem areas of IoT related to security and privacy. Covers all aspects of security Algorithms, protocols and technologies used in IoT have been explained and the security flaws in them analyzed with solutions Discusses ways for achieving better access control and trust in the IoT ecosystem Contributes exhaustive strategic plans to deal with security issues of IoT Gathers contributions from leading-edge researchers from academia and industry Graduates, researchers, people from the industry and security professionals who want to explore the IoT security field will find this book useful. The book will give an in-depth insight in to what has happened, what new is happening and what opportunities exist in the field.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; COMPUTERS / Computer Engineering; COMPUTERS / Information Technology; COMPUTERS / Networking / General